Proton computed tomography using a 1D silicon diode array. Issue 10 (29th September 2016) - Wang, Peng; Cammin, Jochen; Bisello, Francesca; Solberg, Timothy D.; McDonough, James E.; Zhu, Timothy C.; Menichelli, David; Teo, Boon‐Keng Kevin
Abstract : Purpose: Proton radiography (PR) and proton computed tomography (PCT) can be used to measure proton stopping power directly. However, practical and cost effective proton imaging detectors are not widely available. In this study, the authors investigated the feasibility of proton imaging using a silicon diode array. Methods: A one‐dimensional silicon diode detector array (1DSDA) was aligned with the central axis (CAX) of the proton beam. Polymethyl methacrylate (PMMA) slabs were used to find the correspondence between the water equivalent thickness (WET) and 1DSDA channel number. Two‐dimensional proton radiographs were obtained by translation and rotation of a phantom relative to CAX while the proton nozzle and 1DSDA were kept stationary. A PCT image of one slice of the phantom was reconstructed using filtered backprojection. Results: PR and PCT images of the PMMA cube were successfully acquired using the 1DSDA. The WET of the phantom was measured using PR data. The resolution and maximum error in WET measurement are 2.0 and 1.5 mm, respectively. Structures down to 2.0 mm in size could be resolved completely. Reconstruction of a PCT image showed very good agreement with simulation. Limitations in spatial resolution are attributed to limited spatial sampling, beam collimation, and proton scatter. Conclusions: The results demonstrate the feasibility of using silicon diode arrays for proton imaging. Such a device can potentially offer fast image acquisition and high spatial and energy resolution for PR and PCT.